CT and CT-guided Percutaneous Needle Biopsy in Diagnosis of Primary Pulmonary Cryptococcosis in Immunocompetent Patients - Hu, Jibo; Hu, Hongjie; Xie, Susu; Yang, Xiaoming; Zhong, Yaoying; Shi, Yijie (Current Medical Imaging, 2017)
Objective: Primary pulmonary cryptococcosis in immunocompetent patients is very easily misdiagnosed or even missed. Accurate diagnosis of this disease is critical for a timely and proper treatment. This study aims to address the importance of computed tomography (CT) and CT-guided percutaneous needle biopsy for primary pulmonary cryptococcosis in immunocompetent patients. Methods: We retrospectively analyzed clinical features and CT findings of 36 immunocompetent patients with pathologically confirmed primary pulmonary cryptococcosis. CT-guided percutaneous pulmonary needle biopsies were performed in 25 of these patients. Results: Nineteen patients were symptomatic, including cough, chest pain, expectoration, bloody sputum or hemoptysis, and fatigue. Seventeen patients were asymptomatic. CT examinations displayed a single-lobe lesion in 29 cases and multiple-lobe lesions in 7 cases. Lesions were located in the outer zone in 33 cases, and in the middle zone in 3 cases. CT findings were primarily classified into 2 types: solitary nodule (10 cases, 27.8%) and localized multiple miscellaneous nodule or consolidation (26 cases, 72.2%). In addition, air-bronchograms within the lesions, irregular cavitations and halo signs were found in 21, 8 and 10 cases, respectively. Twenty two (88%) of 25 CT-guided percutaneous pulmonary needle biopsies were confirmed to be pulmonary cryptococcosisby pathology. Conclusions: CT findings of localized multiplemiscellaneous nodules or consolidations with airbronchograms, or cavitations, or halo signs, strongly support the presence of primary pulmonary cryptococcosis. CT-guided percutaneous needle biopsy helps with the accurate diagnosis of this disease.
Keywords: Diagnosis